Correlation of Forearm Length with Height of the Tharu Individuals Residing in Nawalparasi District of Nepal - Chaudhary, Deepak; Yadav, Sanjay Kumar; Sah, Surendra Kumar (Medical Journal of Eastern Nepal, 2026)
Background Biometric parameters such as face, fingerprints, length/ breadth of different body parts are necessarily used in modern world in the forensic sciences and in anthropology. Among these, finding stature for identification is the most primary parameter. Objectives The objectives of the study were to measure the height and forearm length of Tharu individuals and establish a correlation between these two parameters. Methods A descriptive study was done in 162 healthy male and163 healthy female adult individuals of tharu community through convenience sampling. Physically challenged and individuals having intercaste marriage known in previous generation were excluded. Forearm length and height of the individuals was measured and the data was analyzed using the R 4.4.1 package. Descriptive quantitative data was reported in Mean±SD. T-test was used to compare the data. Linear regression was used to predict the relation between height and forearm length Results The mean height was found to be 165.5±6.00 cm in male and 154.0±5.70 cm in female and 159.7± 8.21 cm in overall individuals. The mean forearm length was found to be 27.69±1.09 cm in male, 25.15±1.20 cm in female and 26.42± 1.71 cm in overall individuals. Regression equation for overall individuals was found as Height (Ht) = 51.46+ 4.1 X FAL cm and r2= 0.7325 where FAL= Forearm length and r2 is the Co-efficient of Determination. Conclusions There exist relationships between height and forearm length and regression equation can be used in determining the height and forearm length in Tharu individuals.